The Reality of Cloud Computing Technology for Telecom Companies in Saudi Arabia: Trends and Future Plans - Descriptive Study - Al-Faifi, Yahya Ali (Journal of engineering sciences and information technology, 2022)
The study aimes to identify the reality of cloud computing technology for telecom companies in Saudi Arabia, also, to knowing the most important trends and future plans. To achieve the objectives of the study, the researcher used the descriptive approach and the survey method, the questionnaire was used to collect the data, and the sample of study consisted from (250) decision-makers (males and females) responsible for the adoption of the cloud computing technology in telecom companies in Saudi Arabia, including only: directors, heads of sections, and technical staff. The study came out with a set of results, most notably: The respondents strongly agree that the reality of the use of cloud computing by telecom is an important technical and economic choice, and that one of its most important priorities is to maintain the security and privacy of data, and future plans is to develop a national plan for the broadband wireless and investing in information technology infrastructure. In light of the conclusions, the study recommended the decision-makers to adopt cloud computing to maintain the confidentiality of data, and to rely on solutions provided by cyber security to address electronic piracy attacks, while enhancing security to ensure the users’ needs for cloud. The study also recommended the need to allocate government financial resources in partnership with telecom companies. To improve and expand access to fixed and mobile networks, and support them by providing all the privileges and facilities to play this role, it is necessary for telecom companies to possess international Internet connections and the infrastructure necessary to develop cloud computing technology services.